Pengukuran Luas Daun dengan Metode Simpson - Haryadi Haryadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
Since leaf area has important role in photosynthesis and often used in plant growth analysis, it is important to use a method of leaf area measurement that are easy, cheap, accurate and widely applicable. In this research we use Simpson method to measure leaf area of mango, mustard, guava and banana and the result will be used to calculate the ratio of leaf area and long times wide of leaf. The result indicate that the ratio calculated in this method has smaller standard error than the gravimetric method conducted by previous researcher. Furthermore, the ratios of the leafs have small standard error.